Resistência ao cisalhamento de vigas de concreto armado: efeitos das armaduras de cisalhamento e lateral - Menezes, Marina Chagas de (2021)
Since search for efficiency and economy in building structures is increasing, several building components have been industrialized, leading to a significant reduction in costs. The increasing use of welded or tied wire meshes in civil construction, which in beams, in addition to the vertical wires, they have the horizontal wires. This reinforcement can add extra strength to the specimen. Efficient use of meshes requires finding practical solutions to assemble it on site. The behavior of reinforced concrete beams in shear has been analyzed, among other theories, by Shear-Friction Theory (SFT) and Modified Compression Field Theory (MCFT). SFT considers the shear transfer between existing or potential crack planes and MCFT is a smeared cracking model which considers cracked concrete as a new material. In this research, SFT is revisited regarding wire mesh reinforcement as a way to contribute to shear strength. A formulation based on the SFT and a set of tests in literature are used as reference to study the influence of stirrups details and reinforcement rates. In addition, another analytical approach is proposed to assess the shear strength based on Loov's original SFT to deal with lateral reinforcement with any angle, which is confronted with results from experimental tests. To verify the proposed model, as well as to analyze different details of the wire meshes, numerical simulations are performed with DIANA, a finite element analysis software dedicated to the analysis of complex Civil Engineering problems and, in particular, of reinforced concrete structures, with a model based on the MCFT. Effects in shear strength are evaluated, obtaining, with MCFT, results more compatible with the experimental reference, which corroborate the efficiency of the proposed model with the SFT. The order of magnitude of strains and displacements obtained has low changes when detail of the wire mesh is modified. Regarding the ultimate loads, the model did not capture relevant variations by changing the reinforcement detail.